Extensive unilobar primary pulmonary tuberculosis in an infant: A diagnostic dilemma - Chadha Rajiv; Tripathi Rakesh Kumar; Singh Dharmendra; Roy Choudhury S (Journal of Indian Association of Pediatric Surgeons, 2005)
An 11-month old boy presented with frequent episodes of fever and cough over the past 6 months. Investigations revealed a large space-occupying lesion in the upper lobe of the left lung, the remaining lung fields being clear. There was no history of contact with tuberculosis and the tuberculin test was negative. A CT scan of the chest suggested the presence of a pulmonary sequestration in the upper lobe of the left lung. Surgical excision of the affected lobe was performed and histopathological examination of the excised lobe revealed extensive tuberculosis with caseous necrosis. The presentation of progressive primary tuberculosis in infants is discussed along with the diagnostic difficulties in cases with an atypical presentation.